Peeling back the label—exploring sustainable palm oil ecolabelling and consumption in the United Kingdom - Rosemary Ostfeld; David Howarth; David Reiner; Pawel Krasny (Environmental Research Letters, 2019)
Palm oil production has been linked to deforestation, biodiversity loss, and climate change. We explore consumer awareness of palm oil, perceptions of its environmental impact, recognition of ecolabels including the Roundtable on Sustainable Palm Oil (RSPO) ecolabel, and inclusion or avoidance of ecolabels in household shopping using a representative sample of the British population. We find consumer awareness of palm oil to be fairly high (77%), with 41% of those aware of palm oil perceiving it as ‘environmentally unfriendly’, more than double the level of any other vegetable oil examined. However, recognition of the RSPO ecolabel is the same as those who ‘recognize’ a fictitious ecolabel, making recognition indistinguishable from zero. Based on our logistic regression analysis, members of the British population most likely to actively include ecolabelled products in their weekly household shopping are those who are female, from higher socioeconomic groups, spend more than £120 per week on household shopping, and have received a Bachelors degree or higher. Despite clear benefits of environmental certification and ecolabelling, a relatively niche segment of the general population actively includes ecolabelled products in their weekly household shopping. Therefore, we recommend current policies be amended to require companies to source 100% identity preserved certified palm oil that can be traced to the plantation level to avoid having to rely on consumer decisions to enable a shift towards more responsibly-sourced palm oil. Additionally, requiring multinational companies to map and publicly disclose full supply chain information for all global operations, including palm oil suppliers and concessions, could help illuminate and discourage unsustainable practices.